Hubungan Pengetahuan Ibu Dengan Pemilihan Alat Kontrasepsi Dalam Rahim Di Puskesmas Kedungreja - Tintin Gustini; Dede Gantini; Bayu Irianti (2025)
This study was conducted to determine the relationship between maternal knowledge level and IUD selection as a contraceptive method. Objective: To analyze the relationship between maternal knowledge level and Intrauterine Device (IUD) selection at Kedungreja Health Center, Cilacap Regency. Methods: This study used a descriptive correlational design with a cross-sectional approach. The research sample consisted of 37 family planning acceptors at Kedungreja Health Center, Cilacap Regency. The sampling technique used purposive sampling. Data were collected through questionnaires to measure maternal knowledge level about IUD and contraceptive method selection data. Data analysis used statistical tests to determine the relationship between the two variables. Results: The study results showed that the majority of family planning acceptors at Kedungreja Health Center had insufficient knowledge about IUD, namely 19 people (51.4%). Family planning acceptors who chose to use IUD were only 11 people (29.7%) of the total sample. There was a significant relationship between maternal knowledge level and IUD selection as a contraceptive method with a p-value of 0.000 (p < 0.05). Conclusion: The level of maternal knowledge about IUD at Kedungreja Health Center, Cilacap Regency is still low and significantly influences IUD selection as a contraceptive method. Increased education and counseling about IUD need to be implemented to improve maternal knowledge so they can make appropriate decisions in choosing contraceptive methods that suit their needs.